Influence of X-rays and gamma-rays on the mechanical performance of human bone factoring out intraindividual bone structure and composition indices. (January 2022) - Schmidt, Felix N.; Hahn, Michael; Stockhausen, Kilian E.; Rolvien, Tim; Schmidt, Constantin; Knopp, Tobias; Schulze, Christian; Püschel, Klaus; Amling, Michael; Busse, Björn
Abstract: Doses of irradiation above 25 ​kGy are known to cause irreversible mechanical decay in bone tissue. However, the impact of irradiation doses absorbed in a clinical setting on the mechanical properties of bone remains unclear. In daily clinical practice and research, patients and specimens are exposed to irradiation due to diagnostic imaging tools, with doses ranging from milligray to Gray. The aim of this study was to investigate the influence of irradiation at these doses ranges on the mechanical performance of bone independent of inter-individual bone quality indices. Therefore, cortical bone specimens (n ​= ​10 per group) from a selected organ donor were irradiated at doses of milligray, Gray and kilogray (graft tissue sterilization) at five different irradiation doses. Three-point bending was performed to assess mechanical properties in the study groups. Our results show a severe reduction in mechanical performance (work to fracture: 50.29 ​± ​11.49 Nmm in control, 14.73 ​± ​1.84 Nmm at 31.2 ​kGy p ​≤ ​0.05) at high irradiation doses of 31.2 ​kGy, which correspond to graft tissue sterilization or synchrotron imaging. In contrast, no reduction in mechanical properties were detected for doses below 30 ​Gy. These findings are further supported by fracture surface texture imaging (i.e. more brittle fracture textures above 31.2 ​kGy). Our findings show that high radiation doses (≥31.2 ​kGy) severely alter the mechanical properties of bone. Thus, irradiation of this order of magnitude should be taken into account when mechanical analyses are planned after irradiation. However, doses of 30 ​Gy and below, which are common for clinical and experimental imaging (e.g., radiation therapy, DVT imaging, CT imaging, HR-pQCT imaging, DXA measurements, etc.), do not alter the mechanical bending-behavior of bone. Graphical abstract: Image 1